A CBCT Investigation of the Association between Sella-Turcica Bridging and Maxillary Palatal Canine Impaction. (22nd February 2018) - Ortiz, Pamela M.; Tabbaa, Sawsan; Flores-Mir, Carlos; Al-Jewair, Thikriat
Abstract : Objectives . To investigate the association between unilateral/bilateral maxillary canine impaction and sella-turcica bridging using CBCT imaging. Methods . This retrospective comparative study analyzed 76 CBCT images of the craniofacial complex including sella-turcica. The impacted cuspid group consisted of thirty-eight subjects (7 males, 31 females; mean age, 14.6 ± 3.2 years) diagnosed with unilateral (leftn = 14, rightn = 11 ) or bilateral (n = 13 ) palatal canine impaction. The control group included thirty-eight subjects matched by sex (7 males, 31 females; mean age, 19.5 ± 3.6 years) with no impaction. Multinomial logistic regression analysis was used to determine the association between unilateral/bilateral canine impaction and right and left sella-turcica bridging. Results . The prevalence of sella-turcica bridging was 59.3% and 50% in the impacted canine and control groups, respectively. Although the odds for unilateral canine impaction were increased in the right and left sella-turcica bridging groups compared to the controls, the difference was not statistically significant. The risk of bilateral impaction was different between the two sides of sella-turcica bridging, but, again, the findings were not statistically significant. Conclusion . Contrary to previous 2D studies, there is no statistically significant association between unilateral/bilateral palatal canine impaction and sella-turcica bridging when using 3D CBCT.